Risk Taking and Interest Rates : Evidence from Decades in the Global Syndicated Loan Market - Lee, Seung; Liu, Lucy Qian.; Stebunovs, Viktors (Washington, D.C. : International Monetary Fund, 2017)
We study how low interest rates in the United States affect risk taking in the market of crossborder leveraged corporate loans. To the extent that actions of the Federal Reserve affect U.S. interest rates, our analysis provides evidence of a cross-border spillover effect of monetary policy. We find that before the crisis, lenders made ex-ante riskier loans to non- U.S. borrowers in response to a decline in short-term U.S. interest rates, and, after it, in response to a decline in longer-term U.S. interest rates. Economic uncertainty and risk appetite appear to play a limited role in explaining ex-ante credit risk. Our results highlight the potential policy challenges faced by central banks in affecting credit risk cycles in their own jurisdictions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet